Groupes et réseaux féminins à la Cour de Philippe IV d'Espagne (1621-1665) - Alain Hugon (Genre & Histoire)
Historiography has long considered that the women close to Philip IV of Spain (his relatives, mistresses or nuns) were important in political life. But at the same time historians have also highlighted their exclusion from public and government life and even their reclusion in monasteries and convents. Interestingly the king was also seen as « hidden king » to his vassals. In reality, however, some women, directly or indirectly advised him in political life. This article examines their real involvement as advisers as well as questioning the relationship between men and women. It explores in particular the relationships women developed both among themselves within domestic, family, court and religious networks. As well as with the king.